Advancements in the Treatment of Mucopolysaccharidoses: From Established Therapies to Gene Therapy - Joanna Wanat; Wojciech Homa; Aleksandra Warunek; Gabriela Gronowicz; Izabela Dzikowska; Agata Siejka; Daria Stefaniak; Weronika Zielińska; Michał Chról (Journal of Education, Health and Sport)
Introduction and purpose Mucopolysaccharidoses (MPS), a subset of inborn errors of metabolism (IEM), are genetic disorders requiring pediatricians to recognize non-specific symptoms and carefully monitor newborns. Early diagnosis is essential for optimizing therapeutic outcomes. In recent years, significant progress has been made not only in the diagnostic process but also in the development of therapies. Established treatments, such as hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT), have been improved, while advancements in gene therapy have opened new possibilities.